DAMPAK IMPLEMENTASI PROGRAM MAKAN BERGIZI GRATIS TERHADAP PENDAPATAN PELAKU UMKM DI LINGKUNGAN SDN SEMUT - Zulfa Nur Aini; Hendri Hermawan Adinugraha; Ade Gunawan; Rizky Andrean (Adpertens: Jurnal Ekonomi dan Manajemen, 2026)
The Free Nutritious Meal Program is a government policy aimed at improving students’ nutritional quality and reducing parents’ daily food expenses. Its implementation not only affects students as the main beneficiaries but also has the potential to influence economic activities around schools, particularly micro, small, and medium enterprises (MSMEs) that depend on students’ purchasing behavior. This study aims to analyze the impact of the Free Nutritious Meal Program on the income of MSME owners in the SDN Semut area. This research applies a descriptive qualitative method with a case study and literature review approach. Data were collected through semi-structured interviews with five MSME owners around SDN Semut and supported by academic journals, books, and relevant previous studies. The findings show that the program affects MSME income, especially vendors selling main meals who experienced a decline in sales, while snack and beverage sellers remained relatively stable. This occurred because students’ meal needs were fulfilled by the school, encouraging them to reduce purchases and save their pocket money. This study emphasizes the importance of policy evaluation to balance social benefits with local economic sustainability. The originality of this research lies in its focus on school-based MSMEs at the elementary school level.